FDG-PET predicts survival and distant metastasis in oral squamous cell carcinoma - Suzuki, Hidenori; Hasegawa, Yasuhisa; Terada, Akihiro; Hyodo, Ikuo; Nakashima, Tsutomu; Nishio, Masami; Tamaki, Tsuneo (Oral oncology, 2009)
High [ 18F]-2-fluorodeoxyglucose (FDG)-uptake of primary tumor, assessed by pretreatment positron emission tomography (PET), shows poor overall survival of patients after several therapies in various cancers. An association between FDG-uptake and distant metastasis-free survival in oral squamous cell carcinoma (OSCC) has not been assessed so far. An objective of this study is to investigate an association between FDG-uptake and overall survival of OSCC patients, and to ask whether FDG-uptake is related with distant metastasis-free survival in OSCC. Twenty-four patients who underwent both pretreatment FDG-PET and radical surgery without preoperative therapy were enrolled. We used the maximum standardized uptake value (SUVmax) as FDG-uptake. Overall survival, locoregional recurrence-free survival and distant metastasis-free survival were analyzed by Kaplan–Meier method. In univariate survival analysis, patients with SUVmax ≧ 12 exhibited significance in both shorter 3-year overall survival ( p < 0.01) and distant metastasis-free survival ( p < 0.04) than patients with SUVmax < 12. Moreover, by Cox proportional hazards model of multivariate analysis, SUVmax ≧ 12 was found to be independent of clinical T and N categories, and exhibited significance in both shorter 3-year overall survival ( p < 0.02) and distant metastasis- free survival ( p < 0.05) than patients with SUVmax < 12. These results suggest that pretreatment FDG-PET is able to provide both non-invasive and effective information for identifying a high- or low-risk group of OSCC patients with distant metastasis.